Leaves drying kinetics of the species Zanthoxylum sprucei (Rutaceae) and Melampodium divaricatum (Asteraceae) - Ruiz Reyes, Enrique; Baquerizo-Crespo, Ricardo; Macías Pro, Michael; Pin Molina, María José; Pita Gavilanes, Yesther (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The study of the drying of the plants is important for the extraction methods of the active principles, since it provides benefits both for the efficiency and for the stability. The objective of this research is to study the drying kinetics of the leaves of Zanthoxylum sprucei (Rutaceae) and Melampodium divaricatum (Asteraceae) species from the Manabí province. Eight empirical models derived from Fick's law with adjustment and the STATISTICA software as modeler was used. The model was made by applying the ORIGIN Pro fit curve. The kinetic results were obtained experimentally in a laboratory scale tunnel dryer with a temperature of 40°C, at 1 atm of pressure and a speed air of 8.47 m.s-1. To determine the model that best fits the experimental data, it relies on the correlation coefficient (R2), mean square error (ERMS) and chi-square (X2). The mathematical model that best describes the drying process is the logarithmic for Zanthoxylum sprucei and the Wang and Singh model for Melampodium divaricatum.